2017
DOI: 10.1093/humrep/dex096
|View full text |Cite
|
Sign up to set email alerts
|

The long-term prognosis for live birth in couples initiating fertility treatments

Abstract: STUDY QUESTION:What are the long-term chances of having a child for couples starting fertility treatments and how many conceive with ART, IUI and without treatment?SUMMARY ANSWER: Total 5-year live birthrates were strongly influenced by female age and ranged from 80% in women under 35-26% in women ≥40 years, overall, 14% of couples conceived naturally and one-third of couples starting treatments with intrauterine insemination delivered from that treatment.WHAT IS KNOWN ALREADY: Few studies report success rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 21 publications
2
46
1
2
Order By: Relevance
“…However, such information should be age‐specific and accompanied by qualifications about the proportion of women in each age‐group who have embryos available for freezing after a stimulated cycle. Malcau et al . recently published another helpful way of presenting chance of a live birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such information should be age‐specific and accompanied by qualifications about the proportion of women in each age‐group who have embryos available for freezing after a stimulated cycle. Malcau et al . recently published another helpful way of presenting chance of a live birth.…”
Section: Discussionmentioning
confidence: 99%
“…Among women aged under 35 years when they started ART, 80% had a live birth after five years compared with 26% of women aged 40 years or older. In all, 14% of women gave birth after conceiving spontaneously during the five years …”
Section: Discussionmentioning
confidence: 99%
“…The declining fertility potential of women above 30 years of age is well known for all women, causing stress at an age when many women struggle with studies and career or has not yet found a partner to form a family with. A recent study from Denmark showed that fertility drops annually 1%‐4% before the age of 35 years, around 15% between 35 and 40 years and 35% annually above 40 years of age …”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Denmark showed that fertility drops annually 1%-4% before the age of 35 years, around 15% between 35 and 40 years and 35% annually above 40 years of age. 2 The first birth after oocyte freezing, followed by thawing and in vitro fertilization (IVF), was described in 1986 by Chen in South Korea. 3 The slow freezing technique used at that time, had very low survival rate of oocytes and yielded poor results after IVF.…”
Section: Introductionmentioning
confidence: 99%
“…The risks associated with postponing childbearing include age-related decline of female fecundity and impaired success rates of assisted reproductive technologies (Malchau et al, 2017). Increasing paternal age (over 35 years) is associated with lower fertility, an increase in pregnancy-associated complications (higher miscarriage rate, pre-eclampsia and preterm births) and an increase in adverse outcome in the offspring (Sartorius and Nieschlag, 2010).…”
Section: Introductionmentioning
confidence: 99%